2021
DOI: 10.3390/plants10050890
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Development of LTR Retrotransposon-Based Molecular Markers for the Melilotus Genus

Abstract: Melilotus is an important genus of legumes with industrial and medicinal value, partly due to the production of coumarin. To explore the genetic diversity and population structure of Melilotus, 40 accessions were analyzed using long terminal repeat (LTR) retrotransposon-based markers. A total of 585,894,349 bp of LTR retrotransposon sequences, accounting for 55.28% of the Melilotus genome, were identified using bioinformatics tools. A total of 181,040 LTR retrotransposons were identified and classified as Gyps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…RBIP has been used to study the origin of Asian rice varieties and generate markers for marker-assisted breeding of pears ( Kim et al., 2012 ; Roy et al., 2015 ). Genome-wide analysis of RBIP markers in Melilotus genomes revealed high polymorphism information content (PIC), making them valuable tools for genetic improvement of the genus Melilotus ( Ouyang et al., 2021 ).…”
Section: Tes As Molecular Markersmentioning
confidence: 99%
“…RBIP has been used to study the origin of Asian rice varieties and generate markers for marker-assisted breeding of pears ( Kim et al., 2012 ; Roy et al., 2015 ). Genome-wide analysis of RBIP markers in Melilotus genomes revealed high polymorphism information content (PIC), making them valuable tools for genetic improvement of the genus Melilotus ( Ouyang et al., 2021 ).…”
Section: Tes As Molecular Markersmentioning
confidence: 99%
“…The RBIP marker was shown to be duplicated several times during the development of Asian pear cultivars and may provide a comprehensive picture of the complex relationship and evolution of Pyrus species (Jiang et al, 2015). Likewise, genome-wide analysis of RBIP markers in the Melilotus genome revealed considerable polymorphism information content (PIC), indicating that these markers are highly informative and may be used for implementing genetic improvement in the Melilotus genus (Ouyang et al, 2021). Furthermore, RBIP markers used for DNA profiling of Japanese, Chinese, and European pear cultivars revealed that retrotransposons have transposed during Asian pear evolution or reflect the genetic relationship between Asian and European pears.…”
Section: Applications Of Ltr-retrotransposon As Molecular Marker Systemmentioning
confidence: 99%
“…Recently, genome relationships and LTR retrotransposon diversity in three cultivated Capsicum strains were analyzed and a close relationship among the species was revealed (de Assis et al, 2020). Moreover, genome-wide analysis of LTR retrotransposons and their impact on evolution has been explored in several plants (Roulin et al, 2009;Beuléet al, 2015;Giordani et al, 2016;Mascagni et al, 2017;Keidar et al, 2018;Liu et al, 2018;Akakpo et al, 2020;Mascagni et al, 2020;Ouyang et al, 2021). TE amplification is the main mechanism behind plant genome size increase and evolution (Gantuz et al, 2022).…”
Section: Role Of Ltr Retrotransposons In Plant Evolutionmentioning
confidence: 99%
“…A GeneAmp 9700 PCR System was used to perform the PCR (Nadeen et al, 2018). Applied Biosystem Inc.'s (USA) Thermalcycler has a profile that includes an initial 5-minute denaturation at 94°C for 5 min, 30 cycles of 94°C for 30 sec, 50°C for 60 sec, and 72°C for 1 min 30 sec, and a final termination at 72°C for 10 min and chill at 4 o C. (Ouyang et al, 2021).…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%